2016
DOI: 10.1371/journal.pone.0154490
|View full text |Cite
|
Sign up to set email alerts
|

Polyamino-Isoprenic Derivatives Block Intrinsic Resistance of P. aeruginosa to Doxycycline and Chloramphenicol In Vitro

Abstract: Multidrug resistant bacteria have been a worldwide concern for decades. Though new molecules that effectively target Gram-positive bacteria are currently appearing on the market, a gap remains in the treatment of infections caused by Gram-negative bacteria. Therefore, new strategies must be developed against these pathogens. The aim of this study was to select an antibiotic for which a bacterium is naturally resistant and to use an escort molecule to restore susceptibility, similarly to the model of β-lactam/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 38 publications
5
39
0
Order By: Relevance
“…18,19 To better understand whether 3 can act as a disruptor of the transmembrane potential, a real-time efflux assay was utilised. 20 This assay makes use of the membrane-potential-sensitive probe DiSC 3 (5), which when preloaded into bacteria, concentrates in the inner membrane and quenches its own fluorescence. Upon membrane depolarisation, the dye is released and an increase in fluorescence (measured in relative fluorescence units) is observed.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 To better understand whether 3 can act as a disruptor of the transmembrane potential, a real-time efflux assay was utilised. 20 This assay makes use of the membrane-potential-sensitive probe DiSC 3 (5), which when preloaded into bacteria, concentrates in the inner membrane and quenches its own fluorescence. Upon membrane depolarisation, the dye is released and an increase in fluorescence (measured in relative fluorescence units) is observed.…”
Section: Resultsmentioning
confidence: 99%
“…However, enzymes capable of inactivating drugs are only one factor contributing to intrinsic drug resistance in bacteria. Other factors including membrane penetration, efflux mechanisms, and endogenous native substrate competition contribute to intrinsic drug resistance262728. The ability to improve susceptibility of M .…”
Section: Discussionmentioning
confidence: 99%
“…However, Yasuda et al demonstrated that polyamine compounds increase the permeability of the outer membrane of E. coli and potentiate antimicrobial activities of novobiocin and erythromycin, presumably by displacing divalent cations (Ca 2+ and Mg 2+ ) found in the membrane, thus altering its integrity. Although it was shown that geranylamine does not permeabilize the outer membrane, further studies of polyamino‐isoprene derivatives, which are structurally related to 66 and 67 , showed that these compounds tend to destabilize the P. aeruginosa outer membrane . Thus, the antibiotic potentiating activity of this class of EPIs may be due to both EPI and increased permeability of the outer membrane of E. coli , which could be connected to their cationic character at physiological pH.…”
Section: Efflux Pump Inhibitors Of Selected Clinically Relevant Pathomentioning
confidence: 99%
“…Although it was shown that geranylamine does not permeabilize the outer membrane, 234 further studies of polyamino-isoprene derivatives, which are structurally related to 66 and 67, showed that these compounds tend to destabilize the P. aeruginosa outer membrane. 237 Thus, the antibiotic F I G U R E 1 8 Structures of hydantoins potentiating activity of this class of EPIs may be due to both EPI and increased permeability of the outer membrane of E. coli, which could be connected to their cationic character at physiological pH.…”
Section: Geraniol Derivativesmentioning
confidence: 99%